2022
DOI: 10.1186/s41043-022-00320-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of postnatal care service utilization among married women in rural areas in western Ethiopia

Abstract: Background Worldwide studies have shown that three-fourths of the total deaths during the neonatal period occur in the first week of the postnatal period. However, most of these deaths can be prevented with care during pregnancy, childbirth, and postnatal care. According to the 2016 Ethiopia Demographic and Health Survey report, 17% of women in Ethiopia had received postnatal care after childbirth. This study aimed to identify determinants of postnatal care service utilization among married wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
4
4
0
Order By: Relevance
“…The study revealed that women with higher educational levels (SHS and above) were more likely to use PNC services than those without formal education. This finding is consistent with the vast literature in Africa ( Akunga et al, 2014 ; Beyene et al, 2022 ; Kanté et al, 2015 ; Sagawa et al, 2021 ; Sakeah et al, 2018 ; Sisay et al, 2019 ). These similarities can be ascribed to the fact that education acts as a stand-in for knowledge, cognitive abilities, and values, encouraging health-seeking behavior by raising awareness of available health services ( Beyene et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The study revealed that women with higher educational levels (SHS and above) were more likely to use PNC services than those without formal education. This finding is consistent with the vast literature in Africa ( Akunga et al, 2014 ; Beyene et al, 2022 ; Kanté et al, 2015 ; Sagawa et al, 2021 ; Sakeah et al, 2018 ; Sisay et al, 2019 ). These similarities can be ascribed to the fact that education acts as a stand-in for knowledge, cognitive abilities, and values, encouraging health-seeking behavior by raising awareness of available health services ( Beyene et al, 2022 ).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the vast literature in Africa ( Akunga et al, 2014 ; Beyene et al, 2022 ; Kanté et al, 2015 ; Sagawa et al, 2021 ; Sakeah et al, 2018 ; Sisay et al, 2019 ). These similarities can be ascribed to the fact that education acts as a stand-in for knowledge, cognitive abilities, and values, encouraging health-seeking behavior by raising awareness of available health services ( Beyene et al, 2022 ). Another likely explanation is that education gives women more control over their lives and makes it easier for them to interact with their families and seek MHS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…To achieve SDG target 3.2 (i.e., reducing neonatal deaths to at least 12 per 1,000 live births), both countries need to reduce neonatal deaths significantly [ 3 ]. Previous research reveals that if routine postnatal care (PNC) and curative care after deliveries are available to 90% of newborns and their mothers, 10–27% of newborn deaths can be avoided [ 9 ]. According to studies conducted in South Asian nations, a lack of appropriate, suitable, or prompt PNC increases morbidity and mortality [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%